ESP in the Digital Age: Development and Effectiveness Evaluation of an E-Module for English Communication - Maria Evita Sari - (Journal of Linguistics and Language Teaching, 2026)
This study investigates the development and initial evaluation of an e-module titled English for Communication, designed for fourth-semester students of Electronics Engineering Technology (Teknologi Rekayasa Elektronika/TRE) at Politeknik Negeri Batam, Indonesia. The module was developed to bridge the gap between general English instruction and the English for Specific Purposes (ESP) communicative needs of vocational engineering students. Comprising seven thematic units, only Units 1 (Basic Academic Communication) and 2 (Professional and Workplace Communication) were implemented and evaluated in this study. A questionnaire-based evaluation was administered to 84 students to assess content relevance, clarity, learning activities, unit-specific effectiveness, and impact on English communication confidence. Results show overwhelmingly positive responses, with 91.6%–98.9% of respondents rating the module favorably across all indicators. Qualitative feedback identified useful expressions, grammar focus sections, conversation models, and video-based activities as the most valued features. Suggested improvements include expanded grammar exercises, per-unit vocabulary development, subtitle additions to videos, and pronunciation guides. The study contributes to the literature on ESP e-module development for vocational engineering education in Indonesia and provides a formative evaluation basis for the continued development of the remaining five units.